How are Emotional and Physical Demands Associated with Job Dissatisfaction? Moderated by Marital Status - Tirsa Elfira; Rosita Endang Kusmaryani; Yoga Setyo Wibowo (Universitas Ahmad Dahlan, 2020)
Although there has been extensive research on job satisfaction, the theoretical possibilities may be limited. In general, most of the research focuses only on job-demand factors. However, this study focuses on the emotional and physical demands on job satisfaction. Using the 5th wave of IFLS data, this study aims to determine the effect of marital status upon the relationship between emotional and physical demands on employee satisfaction in Indonesia. The results of research from 19,395 Indonesian employees show that marital status is a mediator in the relationship between emotional and physical demands on job satisfaction. The findings suggest that marital status underpins negative outcomes of emotional and physical demands on job satisfaction in Indonesia. Additionally, the present study found that gender differences affect job satisfaction. Traditional role values and gender concepts are discussed.Â demand; physical demands; marital status